Murder by death [videorecording (DVD)] - Simon, Neil; Brennan, Eileen; Capote, Truman, 1924-1984; Coco, James; Falk, Peter, 1927-2011; Guinness, Alec, 1914-2000; Lanchester, Elsa, 1902-1986; Niven, David, 1910-1983; Sellers, Peter, 1925-1980; Smith, Maggie, 1934-; Walker, Nancy, 1922-1992; Winwood, Estelle, 1883-1984; et al. (Columbia Pictures, 2007)
Lionel Twain, an eccentric millionaire, invites five famous detectives to dinner and reveals to them that someone will die at midnight.